THE ROLE OF JOINT STOCK COMPANY IN CIVIL SOCIETY (Spectrum Journal of Innovation, Reforms and Development, 2024)
In the article, the author examines the regulatory framework governing the status of joint-stock companies, a joint-stock company is considered as a subject of civil law. The instability of the legislation on joint-stock companies is noted.